Terpenoid emissions of Mediterranean oaks and their relation to taxonomy - Csiky, O.; Seufert, G. (ECOLOGICAL APPLICATIONS, 1999)
This paper presents results of a laboratory screening study of biogenic emissions from Mediterranean oak species. The experiment aimed at improving our understanding of oak contributions to overall emissions of volatile organic compounds and to the atmospheric chemistry in the Mediterranean area. We measured type and amount of terpenoid emissions (isoprene, mono- and sesquiterpenes) under standard conditions of light and temperature from 14 different Quercus species of Mediterranean and American origin. Tree saplings were exposed in a controlled environment chamber, and leaf-level trace-gas exchange was analyzed with a minicuvette system and gas chromatography, to study the relation between the emission types and emission spectra found and the taxonomy of Quercus. The holarctic group Lepidobalanus and the North American groups Erythrobalanus and Protobalanus were found to be strong isoprene emitters. The Eurasian oak group Sclerophyllodrys emits monoterpenes; Cerris include mostly non-emitters, but also an isoprene and a monoterpene emitter has been found in this group. Results are discussed with respect to their implications for presently used emission scenarios.
The following values have no corresponding Zotero field: pub-location: 1707 H ST NW, STE 400, WASHINGTON, DC 20006-3915 USA publisher: ECOLOGICAL SOC AMER
Keywords: atmospheric chemistry; BEMA (Biogenic Emissions in the Mediterranean Area; Biogenic emission; chemo-taxonomy; isoprene; Mediterranean Region; Monoterpenes; oak taxonomy; oaks; Quercus; terpenoid emissions; trace-gas exchange; volatile organic compounds (VOCs)

Use of the isoprene algorithm for predicting the monoterpene emission from the Mediterranean holm oak Quercus ilex L.: Performance and limits of this approach - Ciccioli, Paolo; Fabozzi, Concetta; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano; Loreto, Francesco; Kesselmeier, Jürgen; Schäfer, Luise; Bode, Kirsten; Torres, Liberto; Fugit, Jean-Luc (Journal of Geophysical Research: Atmospheres, 1997)
The algorithm developed by Guenther et al. [1991] to describe the organic emission of isoprene-emitting plants has been used for predicting monoterpene emission from Quercus ilex L., an evergreen oak typical of the Mediterranean basin. The dependence of monoterpene emission on photosynthetically active radiation and temperature has been verified through laboratory experiments carried out on single leaves as well as through field measurements at branch level. While the algorithm describes well monoterpene emission under stationary state conditions, it is less accurate when rapid fluctuations of light and temperature take place. Because of this, the isoprene algorithm is capable of predicting the response of Quercus ilex L. with an accuracy better than ±25% only in 65% of the environmental situations experienced by the plant. Field and laboratory observations consistently indicate that temperature oscillations can be an important source for the discrepancies between predicted and observed values as they can generate bursts of emission with values twice as high as those predicted by the algorithm. Possible causes generating these effects are analyzed and critically discussed. In spite of the observed limitations, the isoprene algorithm can successfully describe the biogenic emission from Quercus ilex L., and its use is advantageous as it greatly simplifies regional and global emission models, especially if the light dependence of monoterpene emission is proven to be a widespread phenomenon.
Keywords: Biogenic emission; isoprene algorithm; monoterpene (voyant); Quercus ilex; Temperature